THE PROCESS OF PROCESSING CASSAVA INTO MOCAF FLOUR: PROSES PENGOLAHAN SINGKONG MENJADI TEPUNG MOCAF - Sahda, Rona Taqiyya; Sri Hartuti (ROCE : Jurnal Pertanian Terapan, 2025)
Mocaf flour is a local product that can be utilized as an alternative to wheat flour in various food products. Using local food sources, such as cassava, is essential to support food security and reduce dependence on imports. This article is a review examining various methods of processing cassava into Mocaf flour. Mocaf flour is a cassava-based product with the potential to replace wheat flour. The Mocaf processing method consists of several stages, including sorting, peeling, washing, cutting, fermentation, drying, milling, and sieving, which result in high-quality flour with improved texture and flavor. A critical stage in the production of Mocaf flour is the fermentation process. Cassava fermentation can be done using microbes, such as Lactobacillus plantarum bacteria and tape yeast, or through non-microbial fermentation. This fermentation process alters the physicochemical properties of cassava, enhancing viscosity, and rehydration capacity, and reducing its bitterness.